Structural Motifs Involved in Ubiquitin-Mediated Processing of the NF-κB Precursor p105: Roles of the Glycine-Rich Region and a Downstream Ubiquitination Domain - Orian, Amir (American Society for Microbiology, 1999)
The ubiquitin proteolytic system plays a major role in a variety of basic cellular processes. In the majority of these processes, the target proteins are completely degraded. In one exceptional case, generation of the p50 subunit of the transcriptional regulator NF-κB, the precursor protein p105 is processed in a limited manner: the N-terminal domain yields the p50 subunit, whereas the C-terminal domain is degraded. The identity of the mechanisms involved in this unique process have remained elusive. It has been shown that a Gly-rich region (GRR) at the C-terminal domain of p50 is an important processing signal. Here we show that the GRR does not interfere with conjugation of ubiquitin to p105 but probably does interfere with the processing of the ubiquitin-tagged precursor by the 26S proteasome. Structural analysis reveals that a short sequence containing a few Gly residues and a single essential Ala is sufficient to generate p50. Mechanistically, the presence of the GRR appears to stop further degradation of p50 and to stabilize the molecule. It appears that the localization of the GRR within p105 plays an important role in directing processing: transfer of the GRR within p105 or insertion of the GRR into homologous or heterologous proteins is not sufficient to promote processing in most cases, which is probably due to the requirement for an additional specific ubiquitination and/or recognition domain(s). Indeed, we have shown that amino acid residues 441 to 454 are important for processing. In particular, both Lys 441 and Lys 442 appear to serve as major ubiquitination targets, while residues 446 to 454 are independently important for processing and may serve as the ubiquitin ligase recognition motif.